Agronomic advantage of bacterial biological nitrogen fixation on wheat plant growth under contrasting nitrogen and phosphorus regimes - Aasfar, Abderrahim; Meftah Kadmiri, Issam; Azaroual, Salah Eddine; Lemriss, Sanaâ; Mernissi, Najib El; Bargaz, Adnane; Zeroual, Youssef; Hilali, Abderraouf (Frontiers in Plant Science, 2024)
Given their remarkable capacity to convert atmospheric nitrogen into plant-accessible ammonia, nitrogen-fixing microbial species could be a sustainable substitute for chemical nitrogen fertilizers in economically important crops such as wheat. In this study, free nitrogen-fixing strains were isolated and screened from various rhizospheric soils across Morocco, leading to the identification of twenty-two nif-H+ strains belonging to Bacillus sp., Pseudomonas sp., Arthrobacter sp., Burkholderia sp. and a yeast like microorganism. The isolates that possess the nif gene were all selected to assess their PGPR traits. The results showed that most of these selected strains have significant abilities to perform atmospheric nitrogen fixation, notably five strains (NF 516, NF 524, NF 391, NF 430, NF 528) showing a potential rate greater than that (114.21 nmol C2H4) of the reference strain A. chroococcum DSM2286. Moreover, these strains demonstrated proficiency in phosphate solubilization, phytohormone production, and the ability to enhance wheat plant growth under controlled conditions. Subsequently, two specific strains Rhodotorula mucilaginosa NF 516 and Arthrobacter sp. NF 528 were selected for in-depth evaluation, focusing on their ability to reduce chemical nitrogen supply and to evaluate their behavior when used alongside with TSP fertilizer and natural rock phosphate, two different phosphate sources. The findings reveal that the application of Rhodotorula mucilaginosa NF 516 and Arthrobacter sp. NF 528, whether individually or in combination, substantially enhance plant growth and improves nutrient uptake (N and P) under reduced dose of nitrogen and in response to both rock phosphate and TSP. This indicates the significant role of these microorganisms in wheat production under conditions of low nitrogen and complex phosphorus inputs, showcasing their potential to reduce chemical nitrogen fertilization requirements by up to 50% without affecting wheat plant yields. The remaining nitrogen needs, beyond the 50% reduction from chemical fertilizers, were provided by bacterial biological nitrogen fixation (BNF) facilitated by the strains used in our study. This underscores the importance of microbial contributions in providing essential nitrogen for optimal plant growth and emphasizes the role of BNF in sustainable agriculture practices.